OSMANLI PRUSYA BÜYÜKELÇİSİ GİRİTLİ ALİ AZİZ EFENDİ'DE PSİKOLOJİ: NEFS VE AKIL ÖRNEĞİ. - SARITAŞ, Kamil (Electronic Turkish Studies)
Ali Aziz Efendi of Creta is an Ottoman thinker in the XVIIIth century. He is person of rank of Erkan-ı Divan-i Hümayun. He was the first permanent ambassador of Ottoman Empire in the XVIIIth century in Prusya when modernization efforts were seen. His native language was Romaic. He knew Arabic and Persian. He had works in the fields of Islamic thought which are about philosophy, mysticism, law, history, literature and poetry. In this sense, he is a productive Ottoman thinker. Due to these features, trying to understand Ali Aziz Efendi's thoughts means pointing to the frame of mind of Ottaman in the XVIIIth century. Ali Aziz was a thinker who had lived both in Ottoman lands and in Western lands. He wrote most of his works while the ambassador was in the West. In this context, he hazardad an opinion about the quality of interaction between the Ottoman and Western's thoughts. We realize that locating in universal jurisdiction by acting from partial data is causing methodological faults. However, when his properties are considered, it is seen that Ali Aziz is not an ordinary example for understanding the Ottoman thought. Ali Aziz mentioned chapters of psychology admitted areas of philosphy on his works as Makale-i Felsefe, Varidat and Lübbü'l-lübâb fî Merâsîmi'l-âdâb. He focused on the soul and intellect in the field of psychology. He dealt with plant, animal, human and spirit soul as a kinds of soul. He evaluated subject of intellect in terms of biological, cosmological, ethical and epistemological, analyzed intellect in the four section as a potential, inhabitu, actual and acquired. He had similar thoughts with Aristotle, Alexander of Aphrodisias, Alfarabi, Avicenna, Suhrawardi and Averroes on soul and intellect. In this context, it can be expressed that he followed the Peripatetic thoughts.